2022
DOI: 10.1161/circulationaha.122.061612
|View full text |Cite|
|
Sign up to set email alerts
|

A Multicenter, Phase 2, Randomized, Placebo-Controlled, Double-Blind, Parallel-Group, Dose-Finding Trial of the Oral Factor XIa Inhibitor Asundexian to Prevent Adverse Cardiovascular Outcomes After Acute Myocardial Infarction

Abstract: Background: Oral factor XIa (FXIa) inhibitors may modulate coagulation to prevent thromboembolic events without significantly increasing bleeding. We explored the pharmacodynamics, safety, and efficacy of the oral FXIa inhibitor asundexian for secondary prevention after acute myocardial infarction (MI). Methods: We randomized 1601 patients with recent acute MI to oral asundexian 10, 20, or 50 mg or placebo once daily for 6–2 months in a double-blind, placebo-controlled, phase 2, dose-ranging trial. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 31 publications
1
70
0
Order By: Relevance
“…Asundexian (BAY-2433334) is reported to be a selective and reversible factor XIa inhibitor which when used together with aspirin and P2Y12 inhibitor was recently reported to be well tolerated among patients with recent acute myocardial infarction. [4] In this study asundexian was reported to dose dependently inhibit factor Xia and as anticipated did not cause any signi cant increase in bleeding. In addition the incidence of any adverse ischemic events were low among patients receiving asundexian.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Asundexian (BAY-2433334) is reported to be a selective and reversible factor XIa inhibitor which when used together with aspirin and P2Y12 inhibitor was recently reported to be well tolerated among patients with recent acute myocardial infarction. [4] In this study asundexian was reported to dose dependently inhibit factor Xia and as anticipated did not cause any signi cant increase in bleeding. In addition the incidence of any adverse ischemic events were low among patients receiving asundexian.…”
Section: Introductionsupporting
confidence: 65%
“…Based on the observations from this study, several such targets may account for the cardiovascular bene ts of asundexian. [4] One such target of interest was factor XII. Factor XI is reported to be contact activated by factor XII and also involving ampli cation loop by thrombin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a very recent multicenter trial, 1601 patients with recent (within 5 days) acute myocardial infarction (MI) were randomized to oral asundexian at the dosages of 10, 20, or 50 mg or placebo once daily for 6–2 months. Patients received also dual antiplatelet therapy with aspirin plus a P2Y12 inhibitor [ 31 ]. The main safety outcome was bleeding, while the efficacy outcome was a composite of cardiovascular death, MI, stroke, or stent thrombosis comparing pooled asundexian 20 and 50 mg doses vs. placebo.…”
Section: Completed Phase 2 Trialsmentioning
confidence: 99%
“…In a phase 2 dose‐finding clinical trial for the indication stroke prevention in atrial fibrillation, asundexian at doses of 20 mg and 50 mg once daily resulted in near‐complete in vivo FXIa inhibition and in lower rates of bleeding compared with standard dosing of the active comparator, the FXa inhibitor apixaban. 9 Two more phase 2 clinical trials investigating asundexian in acute MI or noncardioembolic stroke are completed: PACIFIC AMI 10 and PACIFIC Stroke, 11 both demonstrating no significant increase in bleeding when added to antiplatelet therapy.…”
mentioning
confidence: 99%